Of fear and strangers : a history of xenophobia - Makari, George (New Haven Yale University Press, 2021)
"Over the last few years, it has been impossible to ignore the steady resurgence of xenophobia. The European migrant crisis and immigration from Central America to the United States have placed Western advocates of globalization on the defensive, and a 'New Xenophobia' seems to have emerged out of nowhere. In this fascinating study, George Makari traces the history of xenophobia from its origins to the present day. Often perceived as an ancient word for a timeless problem, 'xenophobia' was in fact only coined a century ago, tied to heated and formative Western debates over nationalism, globalization, race and immigration. From Richard Wright to Sigmund Freud, Jean-Paul Sartre and Simone de Beauvoir, writers and thinkers have long grappled with this most dangerous of phobias. Drawing on their work, Makari demonstrates how we can better understand the problem that is so crucial to our troubled times."--
Prologue: out of Beirut -- Part I: The origins of xenophobia. 1. In search of Xénos -- 2. Avant la lettre, or the Black Legend -- 3. The first xenophobes -- 4. The Boxer Uprising -- 5. Colonial panic -- 6. Commence the unraveling -- 7. Immigrant boomerang -- 8. The road to genocide -- Part II: Inside the xenophobic mind. 9. Little Albert and the wages of fear -- 10. The invention of the stereotype -- 11. Projection and the negative of love -- 12. The enigma of the other -- 13. Self estrangements -- Part III: The return of the stranger. 14. Why we hate them -- 15. The new xenophobia -- Coda: in the Pyrenees.
Includes bibliographical references and index
George Makari is a psychiatrist, historian, and author. He is Director of the DeWitt Wallace Institute and Professor of Psychiatry at Weill Cornell Medical College.
Print version record.
JSTOR
Keywords: Xenophobia -- History; Ethnic relations -- History; Emigration and immigration -- Social aspects -- History; Discrimination -- History; Nationalism -- History; Xénophobie -- Histoire; Relations interethniques -- Histoire; Émigration et immigration -- Aspect social -- Histoire; Nationalisme -- Histoire; HISTORY / Social History; Discrimination; Emigration and immigration -- Social aspects; Ethnic relations; Nationalism; Xenophobia; History